Sumbawa University Of Technology Infomatrix : Enhancing University Engagement Through An Intelligent Chatbot System - David T. Ndomaina; Shinta Esabella; I Made Widiarta; Nora Dery Sofya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
The aim of this research is to design and implement the chatbot system